Maritime Education Enhancement Through Graduate Experience Analysis - Ahmad Wahid; Tri Cahyadi; Barasa, Larsen; Amrin Amrin (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This qualitative research investigates maritime vocational education effectiveness through comprehensive analysis of thirty graduates from nautical deck engineering, naval marine engineering, and port and shipping engineering programs. The study employs thematic analysis of in-depth interviews to examine professional competency development, sustainability awareness, and industry-academia alignment in maritime education outcomes. Results indicate strong technical competency development (91% high proficiency) and practical training effectiveness (90% satisfaction), while revealing significant gaps in communication skills (68% adequacy), technology integration (61% satisfaction), and sustainability education (69% awareness). Cross-specialization analysis demonstrates varying competency patterns, with port and shipping graduates showing highest business acumen and sustainability awareness, while all specializations require enhanced Maritime English and digital technology competencies. The research identifies communication skills, technology integration, and sustainability education as priority enhancement areas for improving graduate professional preparedness and industry alignment. Findings contribute to maritime education policy development and curriculum enhancement initiatives while providing evidence-based guidance for industry-academia collaboration improvement. The study validates experiential learning approaches in maritime education while highlighting adaptation needs for contemporary industry demands including digitalization, environmental consciousness, and international communication requirements essential for global maritime operations.